Ditregra – an auxiliary program for structural determination of diterpenes. Issue 3 (1997) - Alvarenga Alvarenga, Sandra A. Vestri Sandra A. Vestri; Gastmans Gastmans, Jean Pierre Jean Pierre; Rodrigues Rodrigues, Gilberto do Vale Gilberto do Vale; Emerenciano Emerenciano, Vicente de Paulo Vicente de Paulo
Abstract : This work describes the creation of heuristics rules based on 13 C-NMR spectroscopy that characterize several skeletal types of diterpenes. Using a collection of 2745 spectra we built a database linked to the expert system SISTEMAT. Several programs were applied to the database in order to discover characteristic signals that identify with a good performance, a large diversity of skeletal types. The heuristic approach used was able to differentiate groups of skeletons based firstly on the number of primary, secondary, tertiary and quaternary carbons, and secondly the program searches, for each group, if there are ranges of chemical shifts that identifies specific skeletal type. The program was checked with 100 new structures recently published and was able to identify the correct skeleton in 65 of the studied cases. When the skeleton has several hundreds of compounds, for example, the labdanes, the program employs the concept of subskeletal, and does not classify in the same group labdanes with double bounds at different positions. The chemical shift ranges for each subskeletal types and the structures of all skeletal types are given. The consultation program can be obtained from the authors.